2020
DOI: 10.4314/jasem.v24i6.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Techniques on the Degradability Characteristics of Acacia <i>Acacia hockii</i>) Leaf

Abstract: This experiment was conducted at the Federal University Dutsin-ma Livestock Teaching and Research Farm in Dutsin-ma Local Government area of Katsina State, Nigeria. The study was meant to ascertain the effect of processing techniques on crude protein (CP), acid detergent fiber (ADF) and neutral detergent fiber (NDF) degradation characteristics of three differently processed Acacia hockii leaf meal (ensiled (T1), sun dried (T2) and fresh (T30) incubated in the rumen of five rams at 3, 6, 12, 24 and 48hrs. Acaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…According to Moyo et al (2012) tannins found in leguminous trees are regarded as one natural antioxidant substance. (Ngwa et al, 2002;Mokoboki et al, 2005;Al-soqeer, 2008;Mapiye et al, 2011;Nsahlai et al, 2011;Fuentes et al, 2012;Mbongeni, 2013;Ng'ambu et al, 2013;Zia-Ul-Haq et al, 2013;Brown et al, 2016;Ncube et al, 2017b;Mthethwa, 2018;Gudiso et al, 2019;Abd El-Galil et al, 2018;Gebremeskel et al, 2019;Aruwayo et al, 2020;Otemuyiwa et al, 2020). Sources: (Mapiye et al, 2011;Fuentes et al, 2012;Mbongeni, 2013;Ncube et al, 2017b;Mthethwa, 2018;Abd El-Galil et al, 2018).…”
Section: Nutritional Value and Chemical Composition Of Acacia Speciesmentioning
confidence: 99%
“…According to Moyo et al (2012) tannins found in leguminous trees are regarded as one natural antioxidant substance. (Ngwa et al, 2002;Mokoboki et al, 2005;Al-soqeer, 2008;Mapiye et al, 2011;Nsahlai et al, 2011;Fuentes et al, 2012;Mbongeni, 2013;Ng'ambu et al, 2013;Zia-Ul-Haq et al, 2013;Brown et al, 2016;Ncube et al, 2017b;Mthethwa, 2018;Gudiso et al, 2019;Abd El-Galil et al, 2018;Gebremeskel et al, 2019;Aruwayo et al, 2020;Otemuyiwa et al, 2020). Sources: (Mapiye et al, 2011;Fuentes et al, 2012;Mbongeni, 2013;Ncube et al, 2017b;Mthethwa, 2018;Abd El-Galil et al, 2018).…”
Section: Nutritional Value and Chemical Composition Of Acacia Speciesmentioning
confidence: 99%